MORPHOLOGICAL INDICATORS OF FISH BLOOD - Kh.T. Yuldoshev; M. I. Khushnazarova (Ecominds Press, 2025)
In fish kept in the same environment with a bioecological environment, i.e. weather disturbances, a lot of stagnant water, these indicators were, respectively, metamyelocytic-neutrophil 0.48; segmented neutrophils 1.4; eosinophil 0.0; pseudoeosinophil 2.2; basophil 0.0; pseudobasophil 1.4; monocyte 8.3; lymphocytes 83.5 g/%. In our experiments, an increase in the number of metamyelocytic neutrophils, segmented neutrophils, pseudoeosinophils and lymphocytes was observed, basophils decreased from 2.3 g/% to 0.0, and monocytes decreased from 11.3 g/% to 8.3 G/%.
Keywords: Erythrocyte, 1012/l, Hemocrit, Hemoglobin content in erythrocytes, pg, Average erythrocyte size, μm, Leukocyte x1012/l, Extensive technology, Intensive technology, Artificial pool, Hemoglobin in pool conditions, Limited water pool.